Registration of Two Wheat Germplasm Lines Fixed for Pm58. Issue 2 (18th January 2018) - Wiersma, Andrew T.; Whetten, Rebecca B.; Zhang, Guorong; Sehgal, Sunish K.; Kolb, Frederic L.; Poland, Jesse A.; Mason, R. Esten; Carter, Arron H.; Cowger, Christina; Olson, Eric L.
Abstract : Powdery mildew is a persistent threat to global wheat ( Triticum aestivum L.) production. To broaden the genetic base for resistance to powdery mildew in wheat, germplasm lines U6714‐A‐011 (Reg. No. GP‐1023, PI 682090) and U6714‐B‐056 (Reg. No. GP‐1022, PI 682089) were developed at Michigan State University and are fixed for the novel powdery mildew resistance gene Pm58 . This gene was identified in Aegilops tauschii Coss. accession TA1662, introgressed, and mapped to wheat chromosome 2DS. The two germplasm lines described are BC2 F4 –derived inbred backcrossed lines from a direct cross between TA1662 and the recurrent wheat parent KS05HW14, a hard white winter wheat line adapted to western Kansas. In addition to exhibiting resistant reactions to multiple Bgt isolates with broad virulence profiles, both lines have moderate yield potential and good agronomic characteristics, making them suitable as breeding germplasm. The availability of these lines will enable the incorporation of Pm58 into wheat breeding programs, providing additional genetic variation for resistance to powdery mildew.